2016
DOI: 10.4314/ovj.v6i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic duct lymphography by subcutaneous contrast agent injection in a dog with chylothorax

Abstract: A 4-year-old male Japanese Shiba Inu presented with recurrent chylothorax. The thoracic duct was successfully imaged using computed tomography after the injection of an iodine contrast agent into the subcutaneous tissue surrounding the anus. The thoracic duct was successfully ligated and pericardectomy performed via an open thoracotomy. Pleural effusion improved but relapsed a week after the surgery. A second lymphography revealed a collateral thoracic duct that was not detected during the first lymphography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…10(1): 68-73 visualize the thoracic duct, bone, esophagus, blood vessels, and heart. Unlike the contrast-enhancement CT lymphography and radiographic lymphography (Ando et al, 2011;Birchard et al, 1982;Iwanaga et al, 2016;Johnson et al, 2009;Lee et al, 2012;Millward et al, 2011), the MRTD sequence does not require contrast medium injection into lymph tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10(1): 68-73 visualize the thoracic duct, bone, esophagus, blood vessels, and heart. Unlike the contrast-enhancement CT lymphography and radiographic lymphography (Ando et al, 2011;Birchard et al, 1982;Iwanaga et al, 2016;Johnson et al, 2009;Lee et al, 2012;Millward et al, 2011), the MRTD sequence does not require contrast medium injection into lymph tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to establish reliable methods for the imaging of thoracic and abdominal lymphatic ducts in order to establish the location of the tributaries into which the thoracic duct divides (Ando et al, 2011), thus ensuring that these can be ligated. In veterinary practice, conventional radiographic lymphography and computed tomography (CT) lymphography are used to image the thoracic duct (Birchard et al, 1982;Johnson et al, 2009;Ando et al, 2011;Millward et al, 2011;Lee et al, 2012;Iwanaga et al, 2016). Three-dimensional (3D) reconstruction of CT images is useful for understanding the morphology of the thoracic duct (Ando et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracic duct lymphography has been undertaken under research conditions and in canine patients with chylothorax, using CT and iodine as a contrasting agent. Furthermore, the technique was demonstrated to be beneficial when used post-surgery to check for recurrence [58,59] as it was described as minimally invasive and easy to perform. A similar technique was used to look at feline lymphography.…”
Section: Clinical and Research Investigations Into Soft Tissuesmentioning
confidence: 99%
“…Ando et al (2012) reported an appropriate visualization of the thoracic duct 5 minutes after contrast media injection in a healthy Beagle dog. Iwanaga et al (2016) successfully used this protocol in a Shiba Inu suffering from thoracic duct rupture, with visualization of the duct 10 minutes after injection. In this cat, however, no interpretable visualization of lymphatic system was obtained, with only a few caudal lymph nodes detected.…”
Section: Introductionmentioning
confidence: 99%